Relationship between burnout and obesity: an integrative literature review (Research, Society and Development, 2021)
Objective: to identify scientific evidence on the association between burnout and obesity. Method: Integrative literature review. The guidelines and recommendations of the checklist of the Statement for Reporting Systematic Reviews and Meta-Analyses of Studie (PRISMA) and the PICO strategy were used. The selected articles were analyzed according to the Agency for Healthcare Research and Quality. The databases were: PubMed; CINAHL; Web of Science; Scopus; SciElo; LILACS. Results: One hundred and seven articles were found. The final scope consisted of four studies. The periodicals were in the areas of Public Health, Occupational Health and Environment and Clinical Nutrition. There were three cross-sectional studies and one randomized controlled intervention study. Of the eligible studies, 75% (n=3) were classified at level VI of scientific evidence. However, it is indisputable that there is evidence of a direct or indirect effect of burnout and/or its dimensions on weight gain. Conclusion: The association of burnout and obesity is still incipient, as there were few eligible studies. The levels of evidence in the studies are predominantly due to cross-sectional studies. It is valid to suggest that studies with more robust methodologies be carried out with the theme in question so that the path of causality between burnout and obesity can be better elucidated.